Revisão Sobre a Geoquímica do Berílio nos Materiais Naturais - PULZ, GÊNOVA MARIA; LIMA E CUNHA, MARIA DO CARMO; FORMOSO, MILTON LAQUINTINIE (Pesquisas em Geociências, 1998)
During the middle of 60’s decade an intense investigation about of the beryllium geochemistry was developed, particularly by soviet researchers. After this period only rare studies were carry out. Currently, the economic value combined the possible danger that this element represents to environment have got a research toward a critical review of the geochemistry of this element. The purpose of this article is assemble the dispersed data relative to a beryllium behavior in geologic materials and evaluate its distribution in rocks, soil, water and plants. In addition, this paper comprises the chemistry, mineralogy and occurrence of beryllium in igneous, sedimentary and metamorphic rocks. As it is very important the speciations of Be in endogenous and exogenous processes are described. Some topics on possible impact in the environment and the importance of its biogeochemistry are emphasized. Also some analytical methods for Be are discussed.